1996
DOI: 10.1002/macp.1996.021970925
|View full text |Cite
|
Sign up to set email alerts
|

Anionic polymerization of pentadecanolide. A new route to a potentially biodegradable aliphatic polyester

Abstract: The anionic polymerization of pentadecanolide ( 1 -oxa-2-cyclohexadecanone) initiated with potassium alkoxides was investigated. Polymerization proceeds under mild conditions (tetrahydrofuran, 35 "C ) to form high-molecular-weight polymer (number-average molecular weight a,, up to 100000). The formation of cyclic oligomers, via back-biting reaction, was demonstrated by means of gel-permeation chromatography (GPC) and matrix assisted laser desorption ionisation-time of flight (MALDI-TOF) analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 10 publications
2
25
1
Order By: Relevance
“…4. Unlike the results reported previously 13) , the GPC chromatogram of poly(x-pentadecalactone) displayed a unimodal and symmetric peak, with The thermal properties of poly(x-pentadecalactone) were studied by differential scanning calorimeter (DSC). For all samples, no obvious glass transition was detected within the temperature range studied (from -100 to 130 8C), even after rapid quenching from the melt.…”
Section: Resultscontrasting
confidence: 39%
See 1 more Smart Citation
“…4. Unlike the results reported previously 13) , the GPC chromatogram of poly(x-pentadecalactone) displayed a unimodal and symmetric peak, with The thermal properties of poly(x-pentadecalactone) were studied by differential scanning calorimeter (DSC). For all samples, no obvious glass transition was detected within the temperature range studied (from -100 to 130 8C), even after rapid quenching from the melt.…”
Section: Resultscontrasting
confidence: 39%
“…Nevertheless, relatively high temperatures of 90 -150 8C for bulk polymerization, and long polymerization times were necessary to reach good yields, and only relatively low molecularweight polymers accompanied by small amounts of cyclic and linear oligomers were obtained. Anionic polymerization of the 16-membered lactone, x-pentadecalactone, initiated with potassium alkoxides under mild conditions was reported by Jedliński, et al 13) . No direct correlation between the molecular weight of the resultant polymers and the monomer/initiator ratio was observed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the carbonyl band of PPDL synthesized at 90°C is composed of two overlapped peaks while that sample obtained at 70°C exhibited only one. The overlapped bands, located at 1733 and 1738 cm -1 , have been attributed to the C=O stretching of the crystalline and amorphous phases, respectively, in polyesters like polyhydroxyalkanoates [11,12,13]. This assignment agrees well with results obtained in this work, see thermal characterization section, as the polymer obtained at 90°C had lower cristallinity (is more amorphous) than PPDL prepared at 70°C.…”
Section: Spectroscopic Analysissupporting
confidence: 92%
“…It was reported that 12-and 13-membered lactones could undergo ring-opening polymerization with an alkali metal methoxide as initiator [8] . Anionic polymerization of PDL was initiated with potassium alkoxide by Jedliński et al [9] , but no conclusion on the direct relationship between w M of product and M/I(molar ratio of monomer to initiator) was described. There has been a report about zinc octoate(2-ethylhexanoate) as initiator to polymerize PDL, but the obtained molecular weight was as low as 1500 [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Anionic polymerization of PDL was initiated with potassium alkoxide by Jedliński et al [9] , but no conclusion on the direct relationship between w M of product and M/I(molar ratio of monomer to initiator) was described. There has been a report about zinc octoate(2-ethylhexanoate) as initiator to polymerize PDL, but the obtained molecular weight was as low as 1500 [9] . On the other hand, there have been many studies on enzymatic ring-opening polymerization of macrolactones recently [2,[10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%